Dermatophytosis in a Labrador Pup - A Case Report - Haritha G S,; Siva Rama Krishna P,; Ramesh P,; Prakash Kumar B, (The Indian Veterinary Journal, 2024)
Dermatophytosis is a superficial fungal skin infection in animals that involves skin, hair and nails. It gained public health importance because of its zoonotic nature. The most common dermatophytes responsible for infection in small animals are Microsporumcanis, M gypseumand Trichophyton spp. A three-month old male Labrador pup was presented with clinical signs of patchy alopecia, mild pruritus, blackish discoloration of skin and erythema with crusts on ventral neck. Clinical examination revealed fluorescence on woods lamp test. The tape impression smears collected from the infected areas of skin were examined by lactophenol cotton blue staining which reveals typical macroconidia of the dermatophytes Microsporumspp.,and Trichophyton spp. Topical therapy with Miconazole and Chlorhexidine, adjuvant focal therapy with clotrimazole and oral supplementation of immune booster resulted in complete recovery in four weeks.